Stability in the feeding practices and styles of low-income mothers: questionnaire and observational analyses - Karina Silva Garcia; Thomas G. Power; Ashley D. Beck; Jennifer Orlet Fisher; L. Suzanne Goodell; Susan L. Johnson; Teresia M. O'Connor; Sheryl O. Hughes (BMC, 2018)
Abstract Background During the last two decades, researchers have devoted considerable attention to the role of maternal feeding behaviors, practices, and styles in the development of obesity in young children. Little is known, however, about the consistency of maternal feeding across settings and time. The purpose of this paper was to provide data on this issue by examining the consistency of observed maternal feeding behavior across multiple eating occasions, as well as examine the consistency of observed and self-reported maternal feeding behavior across 18 months. Methods Videotapes from two studies of low-income mothers and their preschool children were coded for feeding practices, dimensions, and styles: a study of 137 low-income, African American and Latina mothers and their children observed during three meals in their homes over a two to three week period, and a study of 138 low-income, Latina mothers observed during a buffet meal in a laboratory setting on two separate occasions 18 months apart. Videotapes from both studies were coded for a wide range of maternal feeding behaviors and strategies. Mothers in the second study also completed three validated, self-report questionnaires on their feeding practices and styles. Results Overall, both observed and self-reported feeding practices and styles showed only moderate levels of stability across meals and over time. Maternal attempts to regulate children's eating showed more stability across meals and over time than the content of general mealtime conversation. Also, greater stability was found in what mothers were trying to get their children to do during the meals than in the strategies they used to influence child behavior. Self-reports of feeding showed greater stability over time than observational measures. Across meals and across 18 months, the stability of general feeding styles was between 40% and 50%. Conclusions The findings demonstrate that maternal feeding behavior was only moderately stable across meals and over time-that is, feeding behavior varied considerably across situations. The lack of high levels of consistency in feeding behavior suggests that situational factors may play a major role in influencing maternal behavior as well. Family-focused childhood obesity programs should focus not only on helping parents change their feeding practices and styles, but also focus on increasing parents' sensitivity to situational factors that affect their approach to feeding their children.